Progress toward Sustainable Development Goals and interlinkages between them in Arctic countries - Qiang Bie; Shijin Wang; Wenli Qiang; Xing Ma; Zhengsheng Gu; Nan Tian (Heliyon, 2023)
The adoption of the 2030 Agenda and its 17 Sustainable Development Goals (SDGs) contribute to addressing the multiple and complex challenges faced by humankind. In particular, the increasing impact of climate change and globalization represent a great challenge for the sustainable development of Arctic countries and efforts are needed to measure, assess, and compare the progress toward SDGs and the trends in this region. This study used 69 indicators closely related to Arctic countries and a composite indicator approach to assess their sustainability performance. SDG interlinkages were also assessed through Spearman's rank order correlation. The results showed that the sustainable development of Arctic countries gradually improved from 2000 to 2020, with increasing scores recorded for 82% of the goals and 73% of the indicators. Overall, significant progress was observed in the SDG 10 (reduction of inequality), SDG 3 (health improvement), and SDG 4 (quality of education). The highest-ranking scores were obtained for poverty reduction (SDG 1), SDG 3, and climate actions (SDG 13) in 2020. Over the 21-year period, Sweden reached the highest overall score for sustainable development, and Russia showed the greatest improvement. Synergies dominated over trade-offs among and within SDGs. SDGs 1, 3, 9, 10, and 11 presented a relatively higher proportion of synergies, while higher proportions of trade-offs were observed for the 8–9, 8–11, 3–12, and 10–12 SDG pairs. The associations of industry development with clean energy use and environmental conservation were strengthened during the study period. However, the performance varied greatly for different indicators, goals, and their correlations among Arctic countries. The results indicate that the main challenges for these countries in relation to SDGs consist in promoting an inclusive economic model as well as sustainable consumption and production patterns.